Respuesta :
Answer: [tex](9x)^{2}-(7)^{2}=(9x-7)(9x+7)[/tex]
Step-by-step explanation:
1. By definition you have that the difference of squares is:
[tex]a^{2}-b^{2}=(a+b)(a-b)[/tex]
2. Given the polynomial:
[tex]81x^{2}-49[/tex]
You can identify that there are two terms whose signs are different and they are perfect squares.
3. Therefore, you have:
[tex]81x^{2}-49=(9x)^{2}-(7)^{2}=(9x-7)(9x+7)[/tex]
Answer:
(9x+7)(9x-7)
Step-by-step explanation:
We have given an expression.
81x²-49
We have to use difference formula which is given in question.
a²-b² =(a+b)(a-b)
We have to write given expression in above formula.
81x²-49 = (9x)²-(7)²
Using given formula , we have
81x²-49 = (9x+7)(9x-7)
Hence, the factors of given expression are (9x-7) and (9x+7).